Beyond Sovereignty. Decentralized Knowledge Production and Legal Normativity in the (Post-)Modern Age - Schimchen, Philip (Teisė, 2025)
n the postmodern era, the decentralized knowledge production, which is inherent to culture itself, becomes radicalized by a hyper-structure of technological networks. This intensifies the need to rethink the mediality of law and the genesis and transformation of legal normativity from a network-oriented point of view. Decentralized knowledge production and forms of practice then become the foundation of legal normativity and legal subjectivity, thus leading to a vital shift in legal theory that calls on abandoning the paradigm of a sovereign legislator and turning to a polycentric, process-oriented and flexible concept of law, where the law reflects its status as a normative knowledge regime in its own operations.
Keywords: Legal Theory; Poststructuralism; Sovereignty; Subjectivity; Network Society; Law and Knowledge